2001
DOI: 10.1073/pnas.231499098
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Jnk signaling pathway by a dual-specificity phosphatase, JSP-1

Abstract: The mitogen-activated protein kinases (MAPKs) are integral to the mechanisms by which cells respond to physiological stimuli, such as growth factors, hormones, and cytokines, and to a wide variety of environmental stresses. The MAPKs, which are stimulated by phosphorylation of a TXY motif in their activation loop, are components of signal transduction cascades in which sequential activation of protein kinases culminates in their activation and their subsequent phosphorylation of various effector proteins that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
77
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 27 publications
2
77
0
Order By: Relevance
“…VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components. Candidates include MKK7 or c-Jun, both of which interact with VHX (31,47). Together, these results indicate that VHX may play a regulatory role in the Jnk or p38 pathways, but they do not yet reveal what phosphoprotein(s) VHX dephosphorylates.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components. Candidates include MKK7 or c-Jun, both of which interact with VHX (31,47). Together, these results indicate that VHX may play a regulatory role in the Jnk or p38 pathways, but they do not yet reveal what phosphoprotein(s) VHX dephosphorylates.…”
Section: Discussionmentioning
confidence: 94%
“…SKRP1 is involved in the regulation of Jnk and interacts with its upstream regulators MKK7 and ASK1 (apoptosis signal-regulating kinase 1) but not with MEKK1 (44,45). Finally, VHX also has been linked to MAP kinase regulation, with a proposed role as a positive regulator of Jnk activation (31,47). VHX associates with p38 and Jnk in vivo but not in vitro (30,47), suggesting that the interaction requires additional components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, we also cloned a new class of DSPs (LMW-DSP1, -DSP2, -DSP4, -DSP6, -DSP10 and -DSP11) from a mouse testis cDNA library and found that they were specifically and abundantly expressed in the testes Aoki et al, 2001). Recently, LMW-DSP2 was found to belong to the subfamily of small DSPs related to the Vaccinia virus VH1 phosphatase (Guan et al, 1991;Aoyama et al, 2001;Shen et al, 2001;Alonso et al, 2002;Chen et al, 2002). The finding that VH1 phosphatase blocked Figure 1 LIF and IL-6 induced mRNA expression of LMW-DSP2 in testicular and hepatoma cells.…”
mentioning
confidence: 95%
“…LMW-DSP2 was found to dephosphorylate and deactivate p38 MAPK and JNK, but not ERK . LMW-DSP2 has also been referred to as VHX (Alonso et al, 2002), JSP1 (Shen et al, 2001) and JKAP (Chen et al, 2002). However, the physiological functions of LMW-DSPs have remained unclear, since they appear to be less efficient than many other MAPK-specific DSPs.…”
mentioning
confidence: 99%